Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2004
DOI: 10.1145/985692.985701
|View full text |Cite
|
Sign up to set email alerts
|

Collision warning design to mitigate driver distraction

Abstract: As computers and other information technology move into cars and trucks, distraction-related crashes are likely to become an important problem. This paper begins to address this problem by examining how alert strategy (graded and singlestage) and alert modality (haptic and auditory) affect how well collision warning systems mitigate distraction and direct drivers attention to the car ahead when it unexpectedly brakes. We conducted two experiments in which drivers interacted with an in-vehicle email system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 21 publications
5
109
0
Order By: Relevance
“…This also extends the results of J.Lee and J. Hoffman [19] where graded warnings provided a greater safety margin, meaning that graded approach may provide an additional safety benefit because it may reduce rear-end collisions induced by sudden braking in response to false warnings. Chen' s study [2] also indicated that provide drivers with traffic situation advisory system can support the driver better participant in critical situation.…”
Section: Collision Ratesupporting
confidence: 80%
“…This also extends the results of J.Lee and J. Hoffman [19] where graded warnings provided a greater safety margin, meaning that graded approach may provide an additional safety benefit because it may reduce rear-end collisions induced by sudden braking in response to false warnings. Chen' s study [2] also indicated that provide drivers with traffic situation advisory system can support the driver better participant in critical situation.…”
Section: Collision Ratesupporting
confidence: 80%
“…More research is necessary to determine the most effective placement, presentation, number, and intensity of a tactile display for rear-end collision warnings. Regardless of driver preference, the present findings, along with previous research (e.g., Lee, Hoffman, & Hayes, 2004;Ferris, Penfold, Hameed, & Sarter, 2006), support tactile warnings over visual and audio warnings for rear-end collision avoidance-some drivers may not have preferred the tactile warnings, but they worked the best to improve brake RT! Interestingly, there is a near-even split between drivers that prefer visual warnings and those that prefer tactile warnings.…”
Section: Driver Preferencessupporting
confidence: 69%
“…One such simulator study examining the effectiveness of audio alerts for an intersection collision warning system showed that drivers receiving the auditory alert had a shorter reaction time, lower speed and reduced crash rate compared to drivers receiving no such alerts (Chang et al 2009). In a distracted driving context, a simulator study by Lee showed that graded warnings provided a greater safety margin and elicited fewer inappropriate responses to poor alarms from drivers (Lee, Hoffman & Hayes 2004). Another simulator study showed that audiovisual collision avoidance warnings elicited the best performance in terms of alerting drivers to potential forward and side object collisions, and older drivers were found to benefit as much as younger drivers from such alerts (Kramer et al 2007).…”
Section: Introductionmentioning
confidence: 99%